Arabidopsis INOSITOL TRANSPORTER4 mediates high-affinity H+ symport of myoinositol across the plasma membrane. - Schneider, Sabine; Schneidereit, Alexander; Gramann, Monika; Sauer, Norbert; et al. (Plant Physiology, 2006)
Four genes of the Arabidopsis (Arabidopsis thaliana) monosaccharide transporter-like superfamily share significant homology with transporter genes previously identified in the common ice plant (Mesembryanthemum crystallinum), a model system for studies on salt tolerance of higher plants. These ice plant transporters had been discussed as tonoplast proteins catalyzing the inositol-dependent efflux of Na(+) ions from vacuoles. The subcellular localization and the physiological role of the homologous proteins in the glycophyte Arabidopsis were unclear. Here we describe Arabidopsis INOSITOL TRANSPORTER4 (AtINT4), the first member of this subgroup of Arabidopsis monosaccharide transporter-like transporters. Functional analyses of the protein in yeast (Saccharomyces cerevisiae) and Xenopus laevis oocytes characterize this protein as a highly specific H(+) symporter for myoinositol. These activities and analyses of the subcellular localization of an AtINT4 fusion protein in Arabidopsis and tobacco (Nicotiana tabacum) reveal that AtINT4 is located in the plasma membrane. AtINT4 promoter-reporter gene plants demonstrate that AtINT4 is strongly expressed in Arabidopsis pollen and phloem companion cells. The potential physiological role of AtINT4 is discussed.